1994
DOI: 10.1182/blood.v84.8.2597.bloodjournal8482597
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD28 and CD40 in human myeloma cells: a comparative study with normal plasma cells

Abstract: CD28 and CD40 are important activation pathways for T and B lymphocytes, respectively. The aim of this study was to determine the phenotype of plasma cells (PCs) and the expression of these two molecules, CD28 and CD40. Therefore, we have compared their expression on normal PCs from bone marrows and tonsils with that of freshly explanted malignant PCs from 31 patients with multiple myeloma (MM) and those from 12 human myeloma cell lines. For this purpose, we first described a new approach to identify plasma ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 0 publications
4
35
0
2
Order By: Relevance
“…investigators (Pellat-Deceunynck et al, 1994;Tong et al, 1994;Pope et al, 2000). Nevertheless, we found that CD40 negative myeloma cells also could effect significantly greater proliferation in the MLR following infection with Ad-CD154, albeit less effectively than Ad-CD154-infected CD40 positive myeloma cells.…”
Section: Discussionmentioning
confidence: 64%
“…investigators (Pellat-Deceunynck et al, 1994;Tong et al, 1994;Pope et al, 2000). Nevertheless, we found that CD40 negative myeloma cells also could effect significantly greater proliferation in the MLR following infection with Ad-CD154, albeit less effectively than Ad-CD154-infected CD40 positive myeloma cells.…”
Section: Discussionmentioning
confidence: 64%
“…In contrast, FCM revealed that virtually all CD138 þþ PB cells were clonal cells. At present, BM and PB malignant PC have been detected by their high expression of CD38 [21]. However, CD38 is expressed on a large variety of other cells, including CD34 þ cells [43].…”
Section: Discussionmentioning
confidence: 99%
“…Malignant PB and BM plasma cells were detected using CD138 (B-B4)-FITC or -PE, a MoAb with high specificity against plasma cells, and CD38-FITC, -PE or -TC MoAbs. As has been previously reported, plasma cells were defined as CD38 þþ /CD138 þþ [21]. PE-or FITC-conjugated MoAbs against several adhesion molecules or B cell antigens were added to each sample.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…CD40 is a member of the Tumour Necrosis Factor (TNF) receptor super family expressed as a type-I transmembrane protein (40 kDa) on both haematopoietic and non-haematopoietic tissues. CD40 is expressed on normal B-cells and at relatively high levels in most B cell malignancies including CLL (Banchereau et al, 1994;Pellat-Deceunynck et al, 1994;Wang et al, 1997). These findings together provide a rationale for targeting this antigen with therapeutic antibodies.…”
mentioning
confidence: 92%